2018
DOI: 10.1080/21645515.2018.1431598
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-10 and TGF-β receptors on dendritic cells enhances activation of effector T-cells to kill cholangiocarcinoma cells

Abstract: Tumor escapes host immune responses by producing immunosuppressive cytokines, such as IL-10 and TGF-β, secreted into the tumor microenvironment. These cytokines play important roles in the suppression of dendritic cell (DC) function, leading to decreased immune responses of the effector CD4 and CD8 T cells. To improve DC functions and enhance cytolytic activity of activated effector T-cells, we suppressed the effect of these cytokines on DCs by using specific neutralizing antibodies that inhibit IL-10 and TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…Elevations of CXCL5, IL-6, and IL-8 and their contributions to dismal prognosis of CCA were reported [15] , [17] , [44] . IL-6 and GROα from CCA-stimulated mesenchymal cells promoted CCA growth [45] , and IL-10 from CCA promoting CCA progression were shown [46] . The induction of MCP-2 in M-CSF–induced MDM has been reported [47] , and we showed higher MCP-2 in TAM-like MDM.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations of CXCL5, IL-6, and IL-8 and their contributions to dismal prognosis of CCA were reported [15] , [17] , [44] . IL-6 and GROα from CCA-stimulated mesenchymal cells promoted CCA growth [45] , and IL-10 from CCA promoting CCA progression were shown [46] . The induction of MCP-2 in M-CSF–induced MDM has been reported [47] , and we showed higher MCP-2 in TAM-like MDM.…”
Section: Discussionmentioning
confidence: 99%
“…They can suppress the activation and proliferation of effector T and B lymphocytes; they can also directly induce pTregs and Bregs (75)(76)(77)(78). In addition, TGF-β and IL-10 inhibit antigenic presentation to stimulate the generation of tolerogenic dendritic cells, which in their turn enable pTreg induction (79)(80)(81)(82)(83). Note that two pTreg populations have been well-described: Th3 and Tr1, featuring high TGF-β, and IL-10 secretion, respectively.…”
Section: Treg Suppressive Activity Mechanismsmentioning
confidence: 99%
“…It has become clear in the last few years that T cell-derived cytokines expressed preferentially by T h 1 cells contribute to joint destruction and inflammatory response in RA, whereas T h 2 cell-associated cytokines may be protective (2,3). However, recent research on T h 17 cells and regulatory T cells (Treg) has demonstrated that an imbalance between T h 1/T h 2/T h 17/Treg cells is important to the pathogenesis of RA (4)(5)(6). Although the origin of RA is unclear, it has been determined that lymphocytes accumulate around the terminal blood vessels of the subsynovial layer prior to the inflammatory response (7).…”
Section: Introductionmentioning
confidence: 99%